Single-dose diclofenac in healthy volunteers can cause decrease in renal perfusion measured by functional magnetic resonance imaging. (27th May 2019) - Hellms, Susanne; Gueler, Faikah; Gutberlet, Marcel; Schebb, Nils Helge; Rund, Katharina; Kielstein, Jan T; VoChieu, VanDai; Rauhut, Sebastian; Greite, Robert; Martirosian, Petros; Haller, Hermann; Wacker, Frank; et al.
Abstract: Objectives: We investigated changes of renal perfusion after topical and oral diclofenac administration in healthy volunteers using functional magnetic resonance imaging (MRI) with arterial spin labelling (ASL). Methods: Twenty-four healthy human participants (21–51 years) underwent 1.5T MRI before and 1 h after a single oral dose of diclofenac (50 mg). Twelve of 24 participants underwent an additional MRI examination following 3-day topical diclofenac administration. For renal perfusion imaging, a flow-sensitive alternating inversion-recovery TrueFISP ASL sequence was applied. Plasma concentrations of diclofenac and serum concentrations of thromboxane were determined. Key findings: After oral diclofenac application, large interindividual differences in plasma concentrations were observed (range <3–4604 nm ). Topical diclofenac application did not result in relevant systemic diclofenac levels (range 5–75 nm ). MRI showed a significant reduction of renal perfusion in individuals with diclofenac levels ≥225 nm (baseline: 347 ± 7 vs diclofenac: 323 ± 8 ml/min/100 g, P < 0.01); no significant differences were observed in participants with diclofenac levels <225 nm . Diclofenac levels correlated negatively with thromboxane B2 levels pointing towards target engagement. Conclusions: Single-dose diclofenac caused a decrease in renal perfusion in participants with diclofenac levels ≥225 nm . We demonstrated that even a single dose of diclofenac can impair renal perfusion, which could be detrimental in patients with underlying chronic kidney disease or acute kidney injury.